Dynamic contrast enhanced MRI for the evaluation of lung perfusion in idiopathic pulmonary fibrosis. Issue 4 (13th October 2022) - Torres, Luis A.; Lee, Kristine E.; Barton, Gregory P.; Hahn, Andrew D.; Sandbo, Nathan; Schiebler, Mark L.; Fain, Sean B.
Background: The objective of this work was to apply quantitative and semiquantitative dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) methods to evaluate lung perfusion in idiopathic pulmonary fibrosis (IPF). Methods: In this prospective trial 41 subjects, including healthy control and IPF subjects, were studied using DCE-MRI at baseline. IPF subjects were then followed for 1 year; progressive IPF (IPFprog ) subjects were distinguished from stable IPF (IPFstable ) subjects based on a decline in percent predicted forced vital capacity (FVC % pred) or diffusing capacity of the lung for carbon monoxide ( D LCO % pred) measured during follow-up visits. 35 out of 41 subjects were retained for final baseline analysis (control: n=15; IPFstable : n=14; IPFprog : n=6). Seven measures and their coefficients of variation (CV) were derived using temporally resolved DCE-MRI. Two sets of global and regional comparisons were made: control versus IPF groups and control versus IPFstable versus IPFprog groups, using linear regression analysis. Each measure was compared with FVC % pred, D LCO % pred and the lung clearance index (LCI % pred) using a Spearman rank correlation. Results: DCE-MRI identified regional perfusion differences between control and IPF subjects using first moment transit time (FMTT), contrast uptake slope and pulmonary blood flow (PBF) (p≤0.05), while global averages did not. FMTT was shorter for IPFprog compared with both IPFstable (p=0.004) and control groups (p=0.023). Correlations were observed between PBF CV and D LCO % pred (rs = −0.48, p=0.022) and LCI % pred (rs = +0.47, p=0.015). Significant group differences were detected in age (p<0.001), D LCO % pred (p<0.001), FVC % pred (p=0.001) and LCI % pred (p=0.007). Conclusions: Global analysis obscures regional changes in pulmonary haemodynamics in IPF using DCE-MRI in IPF. Decreased FMTT may be a candidate marker for IPF progression. DCE-MRI quantitative perfusion and semiquantitative transit time metrics identified regional deficits in IPF lung disease relative to healthy control subjects and in IPF progression https://bit.ly/3swKH6r